Anti-aging activity of Syn-Ake peptide by in silico approaches and in vitro tests - Gok, Bahar; Budama-Kilinc, Yasemin; Kecel-Gunduz, Serda (TAYLOR & FRANCIS INC, 2024)
The increase in the aging population worldwide has led scientists to turn to research to prevent the aging process. In this context, synthetic peptides emerge as candidate molecules for developing new anti-aging products. This study aims to investigate the possible interactions of Syn-Ake, a synthetic peptide, with matrix metalloproteinases (MMPs) and Sirtuin 1 (SIRT1), which are the targets of anti-aging activities with in silico approaches, and to determine the antioxidant activity, and safety profile of the peptide by in vitro methods such as cytotoxicity (MTT) and genotoxicity (Ames) tests. The molecular docking study showed that the docking score energy of MMP receptors was in the order of MMP-13 < MMP-8 < MMP-1. Syn-Ake peptide provided the lowest and the most stable binding to the SIRT1 receptor at -9.32 kcal/mol. Binding interaction and protein-ligand stability of Syn-Ake with MMPs and SIRT1 in a dynamic system were predicted by 50 ns molecular dynamic (MD) simulation studies. The MD results showed that the Syn-Ake peptide remained stable in the active site of MMP-13 and SIRT1 receptors during 50 ns simulations. In addition, the antioxidant activity of Syn-Ake was investigated using diphenyl-2-picril-hydrazine (DPPH) method since it is crucial to remove free radicals that are effective in skin aging. The results revealed the concentration-dependent increased DPPH radical scavenging activity of the peptide. Finally, the safety of the Syn-Ake was investigated, and the safe dose of the peptide was determined. In conclusion, in silico and in vitro analyses show that the Syn-Ake peptide may hold promise in anti-aging formulations with its high efficacy and safety profile.Communicated by Ramaswamy H. Sarma
Keywords: Syn-Ake; molecular docking; MD; antioxidant; toxicity; ACCURATE DOCKING; BINDING; MUTAGENS; MODELS; GLIDE; Biochemistry & Molecular Biology; Biophysics